Charge Accumulation Spectroscopy for Investigating Organic Photovoltaic Stability. Issue 1 (10th November 2016) - Pachoumi, Olympia; Nasrallah, Iyad; Sirringhaus, Henning
Abstract : In order to better understand the degradation mechanisms of inverted organic photovoltaics (OPV), a recently developed spectroscopic technique, charge accumulation spectroscopy, is applied. First, the application of this high‐resolution optical spectroscopy technique to OPV devices is demonstrated by detecting the polaronic absorption in a PTB7 (polythienothiophene derivative):PC70 BM inverted OPV device and then the technique is used to investigate in situ device operational stability. The device instabilities are identified under operational conditions in vacuum leading to significant losses in open‐circuit voltage and fill factor (20% and 10%, respectively, after 80 h of white‐light exposure in vacuum), which are correlated to an interfacial charge‐transfer mechanism between the metal oxide and photoactive layers. It is suggested that under these conditions 0.2% of the PC70 BM molecules become anions due to charge transfer from a highly doped ZnSrO layer leading to device degradation due to enhanced trap‐assisted recombination. Abstract : Charge accumulation spectroscopy (CAS) is demonstrated as a high‐resolution technique for probing charge density in inverted organic photovoltaic devices. The technique is applied to measure the PTB7 (polythienothiophene derivative) polaron absorption and further investigate degradation. Instability with prolonged light exposure under vacuum is identified. CAS and electrical characterization are employed to investigate and discuss the underlying mechanism.